Naturally occurring canine sarcomas: Bridging the gap from mouse models to human patients through cross-disciplinary research partnerships - Klosowski, Marika; Haines, Laurel; Alfino, Lauren; McMellen, Alexandra; Leibowitz, Michael; Regan, Daniel (Frontiers in Oncology, 2023)
In part fueled by support from the National Cancer Institute’s “Cancer Moonshot” program, the past few years have witnessed a renewed interest in the canine spontaneous cancer model as an invaluable resource in translational oncology research. Increasingly, there is awareness that pet dogs with cancer provide an accessible bridge to improving the efficiency of cancer drug discovery and clinical development. Canine tumors share many biological, genetic, and histologic features with their human tumor counterparts, and most importantly, retain the complexities of naturally occurring drug resistance, metastasis, and tumor-host immune interactions, all of which are hard to recapitulate in induced or genetically engineered murine tumor models. The utility of canine models has been particularly apparent in sarcoma research, where the increased incidence of sarcomas in dogs as compared to people has facilitated comparative research that resulted in direct advancements in the treatment of several sarcoma types that have benefited both species. Although spontaneous tumors in pet dogs have become increasingly leveraged in the landscape of sarcoma research, these models remain underutilized, in part due to a lack of more permanent institutional and cross-institutional infrastructure to support partnerships between veterinary and human clinician-scientists. In this review, we provide an updated overview of historical and current applications of spontaneously occurring canine tumor models in sarcoma research, with particular attention to knowledge gaps, limitations, and growth opportunities within these applications. Furthermore, we propose considerations for working within existing veterinary translational and comparative oncology research infrastructures to maximize the benefit of partnerships between veterinary and human biomedical researchers within and across institutions to achieve the ultimate end goal of enhancing the utility and application of spontaneous canine sarcomas in translational oncology research.